Sodium carboxymethylcellulose-zeolite-chitosan copolymer, preparation method, coagulant and application

By adding sodium carboxymethylcellulose, chitosan and zeolite solutions in a specific order in water treatment to form a copolymer of reticular sponge, the metal ion residue and poor mechanical properties of flocculants in the prior art are solved. The problem of this achieves efficient water turbidity removal and rapid settlement effects.

CN119264452AInactive Publication Date: 2025-01-07QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411512334.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the existing water treatment technology, flocculants such as iron salts, aluminum salts and polyacrylamide have metal ion residues and carcinogenicity problems. The natural coagulant chitosan modification process is complex and has high cost. Sodium carboxymethylcellulose The flocculation effect is limited and the mechanical properties are poor.

Method used

By adding sodium carboxymethylcellulose, chitosan and zeolite solutions to the water to be treated in a specific order, a reticular sponge sodium carboxymethylcellulose-zeolite-chitosan copolymer is formed as a coagulant Carry out self-assembly to form an efficient flocculant.

Benefits of technology

It has achieved efficient removal of water turbidity, and the precipitates quickly settle after external disturbance, with a removal rate of more than 90%. It has a simple process and is suitable for lake water treatment of 50-930NTU, with better removal effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264452A_ABST
    Figure CN119264452A_ABST
Patent Text Reader

Abstract

The invention discloses a sodium carboxymethyl cellulose-zeolite-chitosan copolymer, a preparation method, a coagulant and application, and belongs to the field of water treatment. CS, CMC-Na and a zeolite solution are directly added into treated water according to a certain sequence, the CS, CMC-Na and zeolite are subjected to an in-situ self-assembly process, the formed sodium carboxymethyl cellulose-zeolite-chitosan copolymer (CMC-Zeo-CS) has a net-shaped spongy structure, the turbidity removal efficiency of the structure is superior to that of CS, CMC-Na and a traditional coagulant (FeCl3 solution), and the water treatment effect is good. And the formed flower has good mechanical strength, and the coagulation precipitate is high in re-settling speed and good in settling effect after being disturbed and suspended by the outside.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of water treatment, and specifically relates to a sodium carboxymethyl cellulose-zeolite-chitosan copolymer, a preparation method, a coagulant and application. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Coagulation process is the most common water treatment process for removing turbidity from water. The flocculants used in the coagulation process are mainly iron salts, aluminum salts and polyacrylamide. Although they are widely used in the treatment of various sewage and wastewater, the residual and accumulation of metal ions contained in metal salt flocculants in water will seriously affect the survival of aquatic plants and animals, and polyacrylamide flocculants are extremely difficult to degrade. At the same time, monomer acrylamide is also carcinogenic, which poses a huge hidden danger to the ecological safety of natural water bodies. Among natural coagulants, chitosan and its derivatives have the advantages of safety, non-toxicity and biodegradability, but in practical applications, they show disadvantages such as poor water solubility and limited flocculation efficiency. At the same time, various modifications and derivatization methods of chitosan (CS) are used to obtain flocculants with better performance, which have better treatment effects than CS, but there are problems such as complex processes and high costs. Sodium carboxymethyl cellulose (CMC) has stable performance, is easily soluble in water, is biodegradable, biocompatible, and non-toxic. However, its flocculation effect is limited and its mechanical properties are still relatively poor. If it is directly put into water, it will be easily dispersed. Summary of the invention

[0004] In order to solve the deficiencies of the prior art, the purpose of the present invention is to provide a sodium carboxymethyl cellulose-zeolite-chitosan copolymer, a preparation method, a coagulant and an application. In view of the above shortcomings of CS and CMC when used as coagulants, CS, CMC and zeolite solution are directly added to the treated water in a certain order, and the sodium carboxymethyl cellulose-zeolite-chitosan copolymer formed by the in-situ self-assembly process of CS, CMC and zeolite (Zeo) has a mesh sponge-like structure. When the structure is used as a coagulant (CMC-Zeo-CS coagulant), the turbidity removal efficiency is better than that of CS, CMC and traditional coagulants, and the formed flower has good mechanical strength, and the coagulated precipitate is suspended by external disturbance, and the sedimentation speed is fast, and the sedimentation effect is good. At the same time, the preparation process of the present invention is simple and easy to promote.

[0005] In order to achieve the above object, the technical solution of the present invention is:

[0006] In the first aspect, the present invention provides a sodium carboxymethyl cellulose-zeolite-chitosan copolymer, comprising sodium carboxymethyl cellulose, zeolite and chitosan; wherein chitosan and sodium carboxymethyl cellulose form an amide bond, and the sodium carboxymethyl cellulose-zeolite-chitosan copolymer is a copolymer containing hydrogen bonds and amide bonds, and has a network sponge-like structure.

[0007] In a second aspect, the present invention provides a method for preparing the above-mentioned sodium carboxymethyl cellulose-zeolite-chitosan copolymer, comprising:

[0008] After mixing sodium carboxymethyl cellulose solution and water, chitosan solution and zeolite solution are added and mixed, and then sodium carboxymethyl cellulose solution is added and mixed, and stirred to precipitate a copolymer containing hydrogen bonds and amide bonds, namely sodium carboxymethyl cellulose-zeolite-chitosan copolymer.

[0009] In a third aspect, the present invention provides a coagulant comprising the above-mentioned sodium carboxymethyl cellulose-zeolite-chitosan copolymer.

[0010] In a fourth aspect, the present invention provides the use of the sodium carboxymethylcellulose-zeolite-chitosan copolymer or the sodium carboxymethylcellulose-zeolite-chitosan copolymer obtained by the above preparation method or the above coagulant in water treatment.

[0011] In a fifth aspect, the present invention provides a method for water treatment, comprising: directly adding a sodium carboxymethyl cellulose solution, a chitosan solution, and a zeolite solution to water to be treated in a certain order;

[0012] The sequence is to first add the sodium carboxymethyl cellulose solution, then add the chitosan solution and the zeolite solution, mix, and then add the sodium carboxymethyl cellulose solution, mix, and stir.

[0013] The beneficial effects of the present invention are:

[0014] (1) The sodium carboxymethyl cellulose-zeolite-chitosan copolymer synthesized by the present invention has a network sponge structure, and its specific surface area is much larger than that of sodium carboxymethyl cellulose, chitosan and zeolite monomers. When used as a coagulant for water treatment, under the optimal conditions, a removal rate of more than 90% can be achieved after precipitation for 10 minutes, which is much larger than that of adding sodium carboxymethyl cellulose solution, chitosan solution and traditional coagulant FeCl3 solution alone.

[0015] (2) When the present invention is used for water treatment, sodium carboxymethyl cellulose solution, chitosan solution and zeolite solution can be directly added to the water to be treated in a certain order, and a precipitate with a network sponge structure is formed by the in-situ self-assembly process of CS, CMC-Na and zeolite, and the water to be treated is directly suspended and settled. Furthermore, the precipitate formed by coagulation has a fast settling speed after suspension, and the precipitation can be completed again in 3 minutes, and the residual turbidity in the water after re-precipitation is low.

[0016] (3) When treating lake water with turbidity ranging from 50 to 930 NTU, the turbidity removal rate exceeded 90%, and as the turbidity increased, the removal effect became better, reaching a maximum of 98%.

[0017] (4) The method for preparing the coagulant of the present invention is simple and only requires simple mixing.

[0018] (5) Compared with other addition sequences, the removal rate was best achieved by mixing sodium carboxymethyl cellulose solution with water, then adding chitosan solution and zeolite solution, and then adding sodium carboxymethyl cellulose solution. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0020] Figure 1 The morphology diagrams of the raw materials and coagulants in Example 1 of the present invention before and after coagulation are shown; wherein, (a) the morphology diagram of zeolite, (b) the morphology diagram of chitosan, (c) the morphology diagram of CMC, (d) the morphology diagram of the CMC-Zeo-CS coagulant prepared in Example 1 (before coagulation), (e) the morphology diagram of the CMC-Zeo-CS coagulant prepared in Example 1 (after coagulation);

[0021] Figure 2 FT-IR infrared spectra of the raw materials (zeolite, chitosan, CMC) of the present invention, the CMC-Zeo-CS coagulant prepared in Example 1, and the CS-CMC coagulant prepared in Comparative Example 5;

[0022] Figure 3 FT-IR infrared spectra of the suspended matter before coagulation, the CMC-Zeo-CS coagulant before coagulation, and the CMC-Zeo-CS coagulant and the suspended matter after coagulation in Example 1 of the present invention;

[0023] Figure 4 It is a comparison chart of the coagulation removal rate of the present invention and different coagulants; wherein, CMC-Zeo-CS coagulant is the coagulant prepared in Example 1;

[0024] Figure 5 This is a comparison chart of the sediment re-sedimentation effect after coagulation of the present invention and different coagulants; wherein, the CMC-Zeo-CS coagulant is the coagulant prepared in Example 1;

[0025] Figure 6 This is a comparison chart of the removal rate of a lake water with different turbidities according to the present invention; wherein the initial turbidities corresponding to the experimental groups 1-6 are 50NTU, 100NTU, 170NTU, 450NTU, 890NTU, and 930NTU, respectively;

[0026] Figure 7 The influence of different dosing sequences on the coagulation effect;

[0027] Figure 8 The effect of different dosage on coagulation effect;

[0028] Fig. 9 The turbidity removal effects of different addition sequences are shown in Figure 1. (a) raw water, (b) CS+Zeo+CMC+CS, (c) CS+CMC, and (d) CMC+CS+Zeo+CMC prepared in Example 1. (b)-(d) are all supernatants after 10 minutes of precipitation after coagulation test.

[0029] Fig.10 The flowering effects of different addition sequences are as follows: (a) clean water, (b) CMC+CS+Zeo+CMC prepared in Example 1, (c) CS+Zeo+CMC+CS, and (d) CS+CMC. DETAILED DESCRIPTION

[0030] In view of the following problems existing in the prior art: ① CS and CMC-Na have low turbidity removal efficiency ② CS / CMC system has poor mechanical strength ③ CS and CMC-Na modification processes are complex and demanding ④ Traditional coagulants are prone to secondary pollution to the ecological environment. Therefore, the present invention proposes a sodium carboxymethyl cellulose-zeolite-chitosan copolymer. In view of the above shortcomings of CS and CMC-Na when used as coagulants, CS, CMC-Na and zeolite solution are directly added to the treated water. Through the in-situ self-assembly process of CS, CMC-Na and zeolite, the formed sodium carboxymethyl cellulose-zeolite-chitosan copolymer has a mesh sponge structure. When the structure is used as a coagulant, its turbidity removal efficiency is better than that of CS, CMC-Na and traditional coagulants (FeCl3), and the formed flower has good mechanical strength. After the coagulation precipitate is suspended by external disturbance, the sedimentation speed is fast (3min can complete the re-precipitation), and the precipitation effect is good. At the same time, the invention also has the characteristics of simple process and operation for preparing sodium carboxymethyl cellulose-zeolite-chitosan coagulant.

[0031] In a typical embodiment, the present invention provides a sodium carboxymethyl cellulose-zeolite-chitosan copolymer, comprising sodium carboxymethyl cellulose, zeolite and chitosan; wherein chitosan and sodium carboxymethyl cellulose form an amide bond, and the sodium carboxymethyl cellulose-zeolite-chitosan copolymer is a copolymer containing hydrogen bonds and amide bonds, and has a network sponge-like structure.

[0032] In some examples of this embodiment, the sodium carboxymethyl cellulose has a density of 1500-3000 mPa.s and the zeolite has a mesh size of 100-500.

[0033] The sources of sodium carboxymethylcellulose, zeolite and chitosan are not specifically limited and can be purchased through commercial channels. The chitosan used in the present invention adopts MacLean reagent (medium viscosity, 200-400mPa.s, deacetylation degree>90%, cas-9012-76-4), and the zeolite is artificial zeolite 300 mesh (Chinese medicine), ion exchange type.

[0034] In another embodiment, the present invention provides a method for preparing the above-mentioned sodium carboxymethyl cellulose-zeolite-chitosan copolymer, comprising:

[0035] After mixing sodium carboxymethyl cellulose solution and water, chitosan solution and zeolite solution are added and mixed, and then sodium carboxymethyl cellulose solution is added and mixed, and stirred to precipitate a copolymer containing hydrogen bonds and amide bonds, namely sodium carboxymethyl cellulose-zeolite-chitosan copolymer.

[0036] When chitosan solution and zeolite solution are added and mixed, the order of adding chitosan solution and zeolite solution is adding both at the same time, adding chitosan solution first or adding zeolite solution first. Specifically, it can be CMC+CS and Zeo+CMC, CMC+CS+Zeo+CMC or CMC+Zeo+CS+CMC.

[0037] In some examples of this implementation mode, the sodium carboxymethyl cellulose solution is prepared by slowly adding sodium carboxymethyl cellulose into water, stirring continuously at 30-50°C until it is completely dissolved, and heating can accelerate the dissolution rate of CMC. The acetic acid solution is an acetic acid solution with a mass concentration of 1-2%, and the amount of acetic acid should not be too large, otherwise it is easy to cause excessive interference to the pH of the treated water.

[0038] Preferably, the mass volume ratio of sodium carboxymethyl cellulose and water is (1-2):500, in g / mL (the concentration of the sodium carboxymethyl cellulose solution is 0.002-0.004 g / mL).

[0039] In some examples of this embodiment, the chitosan solution is prepared by slowly adding chitosan to an acetic acid solution, stirring continuously at 50-70°C until the chitosan is completely dissolved, and heating can accelerate the dissolution rate of the chitosan. The acetic acid solution is an acetic acid solution with a mass concentration of 1-2%.

[0040] Preferably, the mass volume ratio of chitosan to water is (1-2):500, in g / mL (the concentration of the chitosan solution is 0.002-0.004 g / mL).

[0041] In some examples of this embodiment, the zeolite solution is prepared by slowly adding zeolite into an acetic acid solution, stirring continuously at 50-70°C until the zeolite is completely dissolved, and heating can accelerate the dissolution rate of the zeolite. The acetic acid solution is an acetic acid solution with a mass concentration of 1-2%.

[0042] Preferably, the mass volume ratio of zeolite to water is (1-2):500, in g / mL (the concentration of the zeolite solution is 0.002-0.004 g / mL.

[0043] In some examples of this embodiment, the volume ratio of sodium carboxymethyl cellulose solution, water, chitosan solution, zeolite solution and the added sodium carboxymethyl cellulose solution is (5-10):1:(2-10):(8-20):(5-10), measured in mL:L:mL:mL:mL, preferably (5-10):1:(2-10):(8-12):(5-10), and further preferably (5-10):1:(2-6):(8-12):(5-10).

[0044] In some examples of this embodiment, the sodium carboxymethyl cellulose solution and water are mixed, and the mixing is performed by stirring at 200-600 rad / min for 0.5-3 min.

[0045] In some examples of this embodiment, the chitosan solution and the zeolite solution are added simultaneously and mixed, and the mixing is performed by stirring at 200-600 rad / min for 0.5-3 min.

[0046] In some examples of this implementation manner, the sodium carboxymethyl cellulose solution is then added and mixed, and the mixing is performed by stirring at 200-600 rad / min for 0.5-3 min.

[0047] In some examples of this embodiment, the stirring is performed at 5-50 rad / min for 10-30 min.

[0048] In one embodiment, the present invention provides a coagulant including the above-mentioned sodium carboxymethyl cellulose-zeolite-chitosan copolymer.

[0049] In one embodiment, the present invention provides the use of the sodium carboxymethyl cellulose-zeolite-chitosan copolymer or the sodium carboxymethyl cellulose-zeolite-chitosan copolymer obtained by the above preparation method or the above coagulant in water treatment.

[0050] The turbidity of the treated water body is 10-1500 NTU, preferably 50-930 NTU, and the turbidity removal rate is more than 90%, and the removal effect is better with the increase of turbidity, especially when the turbidity is 900-930 NTU, the turbidity removal rate is more than 98%.

[0051] In one embodiment, the present invention provides a method for water treatment, comprising: directly adding a sodium carboxymethyl cellulose solution, a chitosan solution, and a zeolite solution to water to be treated;

[0052] The sodium carboxymethyl cellulose solution, the chitosan solution and the zeolite solution are directly added to the water to be treated in a certain order;

[0053] The order is to first add the sodium carboxymethyl cellulose solution, then add the chitosan solution and the zeolite solution, mix, and then add the sodium carboxymethyl cellulose solution, mix, and stir;

[0054] Or, adding the sodium carboxymethyl cellulose-zeolite-chitosan copolymer or the coagulant to the water to be treated;

[0055] Furthermore, the volume ratio of the sodium carboxymethyl cellulose solution, water, chitosan solution, zeolite solution and the further added sodium carboxymethyl cellulose solution is (5-10):1:(2-10):(8-20):(5-10), in terms of mL:L:mL:mL:mL, preferably (5-10):1:(2-10):(8-12):(5-10), and further preferably (5-10):1:(2-6):(8-12):(5-10).

[0056] All experiments of the present invention were conducted under the conditions of 1L water sample and an average turbidity of 100NTU.

[0057] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.

[0058] Example 1

[0059] The sodium carboxymethyl cellulose solution (Solution A) is prepared by slowly adding 2 g of sodium carboxymethyl cellulose (content MV250000 (ds=0.7), 1500-3000 mPa.s) into 500 mL of deionized water at 40° C. and continuously stirring until the sodium carboxymethyl cellulose is completely dissolved.

[0060] Chitosan solution (B solution) is prepared by slowly adding 2 g of chitosan (medium viscosity, 200-400 mPa.s) into 500 mL of 2% acetic acid solution at 60° C. and continuously stirring until the chitosan is completely dissolved.

[0061] The zeolite solution (C solution) was prepared by slowly adding 1 g of zeolite (60 mesh) into 500 mL of 2% acetic acid solution at 60° C. and continuously stirring until the zeolite was completely dissolved.

[0062] The order of addition is CMC+CS+Zeo+CMC. Specifically: first, add 6mL solution A to 1L water, stir at 400rad / min for 1min, then add 10mL solution B and 5mL solution C to the above 1L water in sequence, stir at 400rad / min for 1min, then add 6mL solution A to the above 1L water again, stir at 400rad / min for 1min, finally stir at 10r / min for 20min, and precipitate to obtain a copolymer containing hydrogen bonds and amide bonds, namely CMC-Zeo-CS coagulant.

[0063] The above solution A, solution B and solution C are directly added to the lake water according to the above dosage and order, and the precipitate is directly coagulated in the lake water. The turbidity removal rate can reach 94% after 10 minutes of precipitation. The precipitate formed by coagulation settles quickly after suspension, and the precipitation is completed in 3 minutes. After reprecipitation, the residual turbidity in the water is low, as low as 7NTU, and the turbidity removal rate is 93%.

[0064] Example 2

[0065] Different from Example 1, the order of addition is CMC+CS and Zeo+CMC. Specifically:

[0066] The sodium carboxymethylcellulose solution is solution A, the chitosan solution is solution B, and the zeolite solution is solution C. First, 6 mL of solution A is added to 1 L of water and stirred at 400 rad / min for 1 min. Then, 10 mL of solution B and 5 mL of solution C are added to the above 1 L of water at the same time and stirred at 400 rad / min for 1 min. Then, 6 mL of solution A is added to the above 1 L of water again. After precipitation for 10 min, the turbidity removal rate reaches 94%.

[0067] Example 3

[0068] Different from Example 1, the order of addition is CMC+Zeo+CS+CMC. Specifically:

[0069] The sodium carboxymethylcellulose solution is solution A, the chitosan solution is solution B, and the zeolite solution is solution C. First, 6 mL of solution A was added to 1 L of water and stirred at 400 rad / min for 1 min. Then, 5 mL of solution C and 10 mL of solution B were added to the above 1 L of water in sequence and stirred at 400 rad / min for 1 min. Then, 6 mL of solution A was added to the above 1 L of water again. After precipitation for 10 min, the turbidity removal rate reached 93%.

[0070] Embodiment 4:

[0071] Different from Example 1, when the order of addition is CMC+CS+Zeo+CMC, the addition amount is different. Specifically:

[0072] The sodium carboxymethylcellulose solution is solution A, the chitosan solution is solution B, and the zeolite solution is solution C. First, 6 mL of solution A was added to 1 L of water and stirred at 400 rad / min for 1 min. Then, 10 mL of solution B and 10 mL of solution C were added to the above 1 L of water in sequence and stirred at 400 rad / min for 1 min. Then, 6 mL of solution A was added to the above 1 L of water again.

[0073] Embodiment 5:

[0074] Different from Example 1, when the order of addition is CMC+CS+Zeo+CMC, the addition amount is different. Specifically:

[0075] The sodium carboxymethylcellulose solution is solution A, the chitosan solution is solution B, and the zeolite solution is solution C. First, 6 mL of solution A was added to 1 L of water and stirred at 400 rad / min for 1 min. Then, 20 mL of solution B and 5 mL of solution C were added to the above 1 L of water in sequence and stirred at 400 rad / min for 1 min. Then, 6 mL of solution A was added to the above 1 L of water again.

[0076] Comparative Example 1

[0077] Different from Example 1, the order of addition is CS+CMC+Zeo+CS. Specifically:

[0078] The sodium carboxymethylcellulose solution is solution A, the chitosan solution is solution B, and the zeolite solution is solution C. First, 10 mL of solution B was added to 1 L of water and stirred at 400 rad / min for 1 min. Then, 6 mL of solution A and 5 mL of solution C were added to the above 1 L of water in sequence and stirred at 400 rad / min for 1 min. Then, 10 mL of solution B was added to the above 1 L of water again.

[0079] Comparative Example 2

[0080] Different from Example 1, the order of addition is CS+Zeo+CMC+CS. Specifically:

[0081] The sodium carboxymethyl cellulose solution is solution A, the chitosan solution is solution B, and the zeolite solution is solution C. First, 10 mL of solution B was added to 1 L of water and stirred at 400 rad / min for 1 min. Then, 5 mL of solution C and 6 mL of solution A were added to the above 1 L of water in sequence and stirred at 400 rad / min for 1 min. Then, 10 mL of solution B was added to the above 1 L of water again.

[0082] Comparative Example 3

[0083] Different from Example 1, when the order of addition is CMC+CS+Zeo+CMC, the addition amount is different. Specifically:

[0084] The sodium carboxymethylcellulose solution is solution A, the chitosan solution is solution B, and the zeolite solution is solution C. First, 12 mL of solution A was added to 1 L of water and stirred at 400 rad / min for 1 min. Then, 10 mL of solution B and 5 mL of solution C were added to the above 1 L of water in sequence and stirred at 400 rad / min for 1 min. Then, 6 mL of solution A was added to the above 1 L of water again.

[0085] Comparative Example 4

[0086] Different from Example 1, a single flocculant, CS, CMC-Na, zeolite Zeo or traditional coagulant FeCl3 was added, wherein 10 mL of chitosan, 12 mL of CMC (sodium hydroxymethylcellulose), 5 mL of zeolite (2-4‰), and 5 mL of FeCl3 (5%) were added respectively.

[0087] Comparative Example 5

[0088] The difference from Example 1 is that the coagulant is CMC-CS, and the dosage is 12 mL CMC+10 mL CS.

[0089] Comparative Example 6

[0090] The difference from Example 1 is that the coagulant is Zeo-CS, and the dosage is 10 mL CS + 5 mL zeolite.

[0091] Comparative Example 7

[0092] Different from Example 1, the order of addition is CMC+CS+Zeo, specifically:

[0093] The sodium carboxymethylcellulose solution is solution A, the chitosan solution is solution B, and the zeolite solution is solution C. First, 6 mL of solution A was added to 1 L of water and stirred at 400 rad / min for 1 min, and then 10 mL of solution B and 5 mL of solution C were added to the above 1 L of water in sequence and stirred at 400 rad / min for 1 min.

[0094] Comparative Example 8:

[0095] Different from Example 1, the order of addition is CMC+Zeo+CS, specifically:

[0096] The sodium carboxymethyl cellulose solution is solution A, the chitosan solution is solution B, and the zeolite solution is solution C. First, 6 mL of solution A was added to 1 L of water and stirred at 400 rad / min for 1 min. Then, 5 mL of solution C and 10 mL of solution B were added to the above 1 L of water in sequence and stirred at 400 rad / min for 1 min.

[0097] Experiments were conducted on the three reagents (Zeo, CMC, Zeo) in different dosing orders. The final results are as follows: Figure 7 As shown. According to the five addition methods of zeolite + chitosan (Zeo + CMC), CS + Zeo + CMC + CS, CS + CMC + Zeo + CS, CMC + CS + Zeo, CMC + Zeo + CS, no copolymer can be formed, so infrared characterization cannot be performed. When the addition order is CS + Zeo + CMC + CS, CS + CMC + Zeo + CS, CMC + CS + Zeo, CMC + Zeo + CS, when used as a coagulant, the turbidity removal rate is low; only when CMC + CS + Zeo + CMC, CMC + Zeo + CS + CMC copolymers are used as coagulants, the turbidity removal rate is higher than 90% after 10 minutes of precipitation, especially CMC + CS + Zeo + CMC is the best.

[0098] according to Figure 2 The FT-IR spectrum of CS-CMC shows that the 2286 and 2925 cm -1 The peak at 458-855cm disappeared, indicating that there is no obvious stretching vibration of OH in CS-CMC and no hydrogen bonding characteristics. -1 There is no obvious characteristic peak at 1424-1663cm -1 At , the intensity of the characteristic peak of NH bending vibration decreases, which may indicate that the number of amide bonds contained in CS-CMC is smaller than that in CMC-CS-Zeo.

[0099] according to Figure 4From the removal effects of different coagulant combinations on turbidity in lake water, it can be seen that: since Zeo+CMC cannot form a copolymer, the turbidity removal rate of the combination is very low; although a small amount of amide bonds are formed in CS-CMC, its turbidity removal rate is only about 60%; when Zeo, CMC, and CS are used as coagulants alone, their turbidity removal effects are very low; only when the CS-Zeo-CMC copolymer prepared in Example 1 is used as a coagulant, its turbidity removal rate is as high as 98%, which is even higher than that of the traditional coagulant ferrous chloride.

[0100] according to Figure 5 It can be seen from the turbidity after reprecipitation with different coagulants that when the CS-Zeo-CMC copolymer prepared in Example 1 of the present application is used as a coagulant, the precipitate after coagulation can be resuspended for only 3 minutes to complete precipitation again, and the turbidity after reprecipitation can be reduced to below 10NTU, which is lower than the effect of the traditional coagulant ferrous chloride.

[0101] according to Figure 6 From the comparison chart of the removal rates of a lake water with different turbidities of the present invention, it can be seen that when lake water with turbidity ranging from 50 to 930 NTU is treated, the turbidity removal rate exceeds 90%, and the removal effect is better as the turbidity increases.

[0102] according to Figure 8 The experimental results of different dosages of the three reagents are shown in the figure. It can be seen that under the condition of the best reagent addition sequence (CMC+CS+Zeo+CMC), changing the dosage of the three reagents has a significant effect on the coagulation effect, especially when CMC and CS are excessive, the coagulation effect will be significantly reduced. When the dosage of CMC+CS+Zeo+CMC is 6+10+5+6mL, the turbidity removal rate can reach 94%; without changing the addition sequence and dosage of CMC and CS reagents, when the zeolite dosage is 10mL, the turbidity removal rate drops to 88%, and when the dosage of CMC or CS is doubled, the turbidity removal drops to 35% and 62%.

[0103] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A sodium carboxymethylcellulose-zeolite-chitosan copolymer, characterized in that: The invention comprises sodium carboxymethyl cellulose, zeolite and chitosan; wherein chitosan and sodium carboxymethyl cellulose form an amide bond, and the sodium carboxymethyl cellulose-zeolite-chitosan copolymer is a copolymer containing hydrogen bonds and amide bonds and presents a mesh sponge-like structure.

2. The sodium carboxymethyl cellulose-zeolite-chitosan copolymer according to claim 1, characterized in that: The concentration of the sodium carboxymethyl cellulose solution is 0.002-0.004 g / mL; The concentration of the chitosan solution is 0.002-0.004 g / mL; The concentration of the zeolite solution is 0.002-0.004 g / mL.

3. The sodium carboxymethylcellulose-zeolite-chitosan copolymer according to claim 2, characterized in that: The volume ratio of sodium carboxymethyl cellulose solution, chitosan solution, zeolite solution and the added sodium carboxymethyl cellulose solution is (5-10):(2-10):(8-20):(5-10), in terms of mL:mL:mL:mL, preferably (5-10):(2-10):(8-12):(5-10), and more preferably (5-10):(2-6):(8-12):(5-10).

4. The method for preparing the sodium carboxymethyl cellulose-zeolite-chitosan copolymer according to any one of claims 1 to 3, characterized in that: include: After mixing sodium carboxymethyl cellulose solution and water, chitosan solution and zeolite solution are added and mixed, and then sodium carboxymethyl cellulose solution is added and mixed, and stirred to precipitate a copolymer containing hydrogen bonds and amide bonds, namely sodium carboxymethyl cellulose-zeolite-chitosan copolymer.

5. The preparation method according to claim 4, characterized in that: When the chitosan solution and the zeolite solution are added and mixed, the order of adding the chitosan solution and the zeolite solution is adding both at the same time, adding the chitosan solution first, or adding the zeolite solution first.

6. The preparation method according to claim 4, characterized in that: The chitosan solution is prepared by slowly adding sodium carboxymethyl cellulose into water and continuously stirring at 30-50° C. until the sodium carboxymethyl cellulose is completely dissolved. Slowly add chitosan into the acetic acid solution at 50-70°C and continue stirring until it is completely dissolved; The zeolite solution is prepared by slowly adding zeolite into an acetic acid solution at 50-70° C. and continuously stirring until the zeolite is completely dissolved; Preferably, the mass fraction of the acetic acid solution is 1-2%; Preferably, the concentration of the sodium carboxymethyl cellulose solution is 0.002-0.004 g / mL; Preferably, the concentration of the chitosan solution is 0.002-0.004 g / mL; Preferably, the concentration of the zeolite solution is 0.002-0.004 g / mL.

7. The preparation method according to claim 4, characterized in that: The volume ratio of the sodium carboxymethyl cellulose solution, water, chitosan solution, zeolite solution and the added sodium carboxymethyl cellulose solution is (5-10):1:(2-10):(8-20):(5-10), in terms of mL:L:mL:mL:mL, preferably (5-10):1:(2-10):(8-12):(5-10), and more preferably (5-10):1:(2-6):(8-12):(5-10); Preferably, the sodium carboxymethyl cellulose solution and water are mixed under the stirring condition of 200-600 rad / min for 0.5-3 min; Preferably, the chitosan solution and the zeolite solution are added and mixed, and the mixing condition is stirring at 200-600 rad / min for 0.5-3 min; Preferably, the sodium carboxymethyl cellulose solution is added and mixed, and the mixing condition is stirring at 200-600 rad / min for 0.5-3 min; Preferably, the stirring is performed at 5-50 rad / min for 10-30 min.

8. A coagulant, comprising the sodium carboxymethyl cellulose-zeolite-chitosan copolymer according to any one of claims 1 to 3 or the sodium carboxymethyl cellulose-zeolite-chitosan copolymer obtained by the preparation method according to claims 4 to 7.

9. Use of the sodium carboxymethyl cellulose-zeolite-chitosan copolymer according to any one of claims 1 to 3 or the sodium carboxymethyl cellulose-zeolite-chitosan copolymer obtained by the preparation method according to any one of claims 4 to 7 or the coagulant according to claim 8 in water treatment.

10. A method for water treatment, characterized in that: include: The sodium carboxymethyl cellulose solution, the chitosan solution and the zeolite solution are directly added to the water to be treated in a certain order; The order is to first add the sodium carboxymethyl cellulose solution, then add the chitosan solution and the zeolite solution, mix, and then add the sodium carboxymethyl cellulose solution, mix, and stir; Preferably, the volume ratio of the sodium carboxymethyl cellulose solution, water, chitosan solution, zeolite solution and the added sodium carboxymethyl cellulose solution is (5-10):1:(2-10):(8-20):(5-10), in terms of mL:L:mL:mL:mL, preferably (5-10):1:(2-10):(8-12):(5-10), more preferably (5-10):1:(2-6):(8-12):(5-10); Preferably, the concentration of the sodium carboxymethyl cellulose solution is 0.002-0.004 g / mL; The concentration of the chitosan solution is 0.002-0.004 g / mL; The concentration of the zeolite solution is 0.002-0.004 g / mL.

Citation Information

Cited By

  • High-survival-rate fry breeding method

    CN122439639A